Building ac data logger via pc sound card [compact disc] - 250906 Siti Sarah Safaai (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Sains (Fizik Industri )) - Universiti Teknologi Malaysia, 2006